(untitled) (Bangladesh Journal of Infectious Diseases, 2025)
Background: Helicobacter pylori induced gastritis involves dense mucosal granulocyte infiltration, driven by pro-inflammatory cytokines like interleukin-8 (IL-8), with cytokine gene polymorphisms influencing secretion levels. Objective: The study investigated the association of IL-8–251 A/T polymorphism (Three genotypes: A/A, A/T, T/T) with gastroduodenal diseases in Helicobacter pylori infected patients. Methodology: This was a prospective observational study that recruited gastritis patients who underwent upper gastrointestinal endoscopic examinations at the outpatient department of Gastroenterology at Bangladesh Medical University, Dhaka, Bangladesh (Former: Bangabandhu Sheikh Mujib Medical University (BSMMU)) and Dhaka Medical College Hospital in Dhaka, Bangladesh, from 2015 to 2020. Patients who received Helicobacter pylori eradication treatment in the previous 2 months, elderly individuals aged more than 65 years and those who had severe medical or surgical illnesses or had used proton pump inhibitors, nonsteroidal anti-inflammatory drugs, colloidal bismuth compounds, or antibiotics within 4 weeks of enrollment were excluded from the study. The Helicobacter pylori infection was identified using a rapid urease test, PCR of the ureC gene, and histological examination. Grading of gastritis was diagnosed through histopathological analysis and was graded as normal gastric mucosa (Grade - 0, I), Chronic gastritis (Grade-II), and Chronic active gastritis (Grade-III). Interleukin-8 (IL-8) gene polymorphism at the -251 position was detected by Polymerase Chain Reaction restriction fragment length polymorphism. Results: The frequencies of IL-8 T/A, A/A genotypes and A carrier were significantly higher in the Helicobacter pylori -infected population, whereas T/T genotypes were predominant among the counterparts (P =0.001). The IL-8 A allele carriers with Helicobacter pylori infection had an increased risk of developing gastritis (P=0.003). Most Grade III gastritis patients (93.7%) were infected with Helicobacter pylori. The frequency of A carrier was much higher (93.3%) than the T/T genotype among Helicobacter pylori -infected chronic active gastritis patients (Grade III), whereas the T/T genotype was observed in 100.0% of Helicobacter pylori-negative Grade III gastritis population. Conclusion: The Helicobacter pylori-infected patients carrying the A allele may increase the risk of gastritis, whereas the T/T genotype is protective. Bangladesh Journal of Infectious Diseases, June 2025;12(1):85-92